2022
DOI: 10.1155/2022/3880687
|View full text |Cite|
|
Sign up to set email alerts
|

Research on Polycaprolactone-Gelatin Composite Scaffolds Carrying Nerve Growth Factor for the Repair of Spinal Cord Injury

Abstract: Objective. This study was to investigate the mechanism of action of polycaprolactone/gelatin (PCL/GE) composite fiber scaffold with nerve growth factor (NGF) in the recovery of spinal cord injury (SCI). Methods. Sixty female Sprague-Dawley (SD) rats were randomly assigned to the negative control group, the positive control group, the PCL/GE scaffold group, and the collagen-binding structural domain nerve growth factor (CBD-NGF)/PCL/GE scaffold group, with 15 rats in each group. Spinal cord transection was used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…BDNF and NGF are a neurotrophic factor and nerve growth factor, respectively, that promote the regeneration, plasticity, and re-myelination of neurons in the nervous system in pathological states caused by disease or trauma [ 55 58 ]. Studies have shown neuroprotective effects by upregulating BDNF [ 59 ] and NGF [ 60 ] in the injured spinal cord. NSC grafts exert a neuroprotective and regenerative effects by upregulating BDNF [ 61 ] and NGF[ 62 ] in injured spinal cords.…”
Section: Discussionmentioning
confidence: 99%
“…BDNF and NGF are a neurotrophic factor and nerve growth factor, respectively, that promote the regeneration, plasticity, and re-myelination of neurons in the nervous system in pathological states caused by disease or trauma [ 55 58 ]. Studies have shown neuroprotective effects by upregulating BDNF [ 59 ] and NGF [ 60 ] in the injured spinal cord. NSC grafts exert a neuroprotective and regenerative effects by upregulating BDNF [ 61 ] and NGF[ 62 ] in injured spinal cords.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, NGF is neuroprotective for several neural populations [64], including sensory spinal tracts such as the fasciculus gracilis and fasciculus cuneatus, and the ventral and lateral spinothalamic tracts [66]. Finally, several studies underline that therapies able to increase endogenous NGF (e.g., via genetically modified cells or tissue engineering scaffolds [67] or by local NGF administration [68][69][70]) can improve the functional outcome in SCI [10,67].…”
Section: Discussionmentioning
confidence: 99%
“…In vitro cultures showed that AGP3 hydrogel exhibited excellent biocompatibility and promoted the differentiation of NSCs toward neurons while inhibiting the over proliferation of astrocytes. In vivo implantation of AGP3 hydrogel completely covered the tissue defects and reduced the injured luminal area ( Yang B. et al, 2022 ; Yang S. et al, 2022 ).…”
Section: Application Of Hydrogels In Sci Repairmentioning
confidence: 99%